S100 calcium-binding protein B in older patients with depression treated with electroconvulsive therapy. (December 2019) - Carlier, Angela; Boers, Kimberly; Veerhuis, Robert; Bouckaert, Filip; Sienaert, Pascal; Eikelenboom, Piet; Vandenbulcke, Mathieu; Stek, Max L.; van Exel, Eric; Dols, Annemiek; Rhebergen, Didi
Highlights: Higher S100B levels are associated with higher remission rates in depressed patients. Serum S100B levels do not change after ECT. S100B is not likely to be a state marker of depression. Serum S100B levels could be of importance as biological marker of responsiveness to ECT. Abstract: Background: Increasing evidence suggests that glial mediated disruption of neuroplasticity contributes to depression. S100 calcium-binding protein B (S100B) promotes neuronal protection in nanomolar concentrations. Studies on its possible role as a treatment outcome marker in affective disorders are limited. Recent evidence suggests a putative role for S100B as a state marker of illness activity as it is found elevated in episodes of major depression. Aim: To investigate whether higher S100B is associated with favourable treatment outcome following electroconvulsive therapy (ECT) and to further explore whether S100B reflects a state marker of depression activity. Methods: Serum S100B samples, at baseline and post-ECT and clinical assessments including Montgomery Åsberg Rating scales were collected in 91 older depressed patients (mean age: 73.0 years), referred for ECT. Change in pre- and post-ECT S100B was compared between remitters and nonremitters. Logistic and Cox regression analyses were used to determine whether S100B was associated with remission of depression. Results: Patients with S100B levels in the intermediate tertile, that is, between 33 ng/L and 53 ng/L, had higher odds on remission, odds ratio: 5.5 (95%Confidence Interval (CI): 1.55–19.20, p = <0.01), and were more likely to remit from depression over time, hazard ratio: 1.96 (95%CI: 1.04–3.72, p = 0.04), compared with patients in the lowest tertile. There was no significant decrease in levels of S100B after ECT in both remitters and nonremitters. Conclusion: Our findings demonstrate that patients with higher S100B levels at baseline were more likely to remit from depression suggesting an association between higher S100B and responsiveness to ECT. Next, S100B levels do not decrease after remission, suggesting S100B is not a state marker of depression. S100B is not capable of predicting treatment outcome by itself, further research may combine outcome markers.